An Exploration of Patient Satisfaction after Total Knee Replacement Surgery - Klem, Nardia-Rose (Curtin University, 2021)
There is a paucity of investigation into the patient’s perspective of outcomes after total knee replacement (TKR). In particular, there is a lack of understanding of what patient satisfaction means to the individual and how this intersects with outcomes of pain and function. To increase the proportion of people experiencing a meaningful benefit from TKR, a better understanding of patient satisfaction is needed at the level of the individual. This thesis sought to gain the patient’s perspective on satisfaction, which can inform targeted solutions to patient problems.